Pemberdayaan Masyarakat Desa Melalui Pembuatan Sabun Cair Di Desa Singkalanyar Prambon Nganjuk - Munawi, Hisbulloh Ahlis; Santoso, Rachmad; Nevita, Ary Permatadeny; Hapsari, Kustriwi Ratnaning (Jurnal Pengabdian Masyarakat Nusantara, 2021)
The training partner is the PKK group in Singkalanyar Village, Prambon District, Nganjuk Regency. The problem faced by partners so far is that partners do not get training that is easy to apply, besides the training that partners get is not a training that is directly related to family needs. Another problem faced by partners during this pandemic is an increase in family spending related to increasing hygiene standards, including soap spending. The purpose of this PkM is to provide training in making liquid soap for family needs, so it will be able to reduce expenses, especially in soap consumption, and it is hoped that later it can become a source of community income. This service activity begins with a field survey followed by online training by providing videos about making liquid soap. Furthermore, the activity was continued with offline training in the form of hands-on practice with partner groups. In this offline training, related training was also conducted in product marketing. The next activity is monitoring/reviewing the sustainability of the training activities that have been carried out. The trainees are very enthusiastic in participating in the training, because this training is an applicable training, it does not require special skills and special equipment and the results can be directly used by partner groups, especially for personal consumption.